Case management programs in emergency department to reduce frequent user visits: a systematic review - Raffaele, Di Mauro (Acta Biomed, 2019)
BACKGROUND AND AIM: Inappropriate visits to the Emergency Department (ED) by frequent users (FU) are a common phenomenon because this service is perceived as a rapid and concrete answer to any health and social issue not necessarily related to urgent matters. Could Case Management (CM) programs be a suitable solution to address the problem? The purpose is to examine how CM programs are implemented to reduce the number of FU visits to the ED. METHODS: PubMed, CINAHL and EMBASE were consulted up to December 2018. This review follows PRISMA guidelines for systematic review, as first outcomes were considered the impact of CM interventions on ED utilization, costs and composition of teams. RESULTS: Fourteen studies were included and they showed patients with common characteristics but the FU definition wasn’t the same. Twelve studies provided a reduction of ED utilization and seven studies a cost reduction. The main tool used is the individual care plan with telephone contact, supportive group therapy, facilitated contacts with healthcare providers and informatics system for immediate identification. The CM team composition is heterogeneous, even if nurses are considered the most used professional figures. CONCLUSIONS: In contrast with a standardized method, a customized approach of CM program helps frequent users in finding an appropriate answer to their needs, thus decreasing inappropriate visits to the ED. (www.actabiomedica.it)